PENGARUH HEDONIC CONSUMPTION, LINGKUNGAN TOKO DAN POTONGAN HARGA TERHADAP IMPULSE BUYING DENGAN EMOSI POSITIF SEBAGAI VARIABEL INTERVENING PADA D'CHICKEN SAMBAL BAKAR SITUBONDO - Utami, Nanda Siti Nur; Soeliha, Siti; Ciptasari, Ayu Dita Windra (Fakultas Ekonomi dan Bisnis, 2024)
The culinary business is one of the businesses booming and has quite a large development potential. This is illustrated by the number of culinary entrepreneurs who are successful in making profits in their businesses. The aim of this research is to analyze and test the influence of Hedonic Consumption, Store Environment, and Price Discounts on Impulse Buying with Positive Emotions as an Intervening Variable. The population in this research is consumers of D'Chicken Sambal Bakar Situbondo. The sampling technique in this research is simple random sampling. Data analysis and hypothesis testing in this research used the advanced Partial Least Square - Structural Equation Model (PLS-SEM), a robust and reliable method for complex data analysis. The results of the direct influence hypothesis test using the Smart PLS 3.0 application reveal significant insights. Hedonic consumption has a significant positive effect on positive emotions. The store environment, while not significant, has a positive effect on positive emotions. Price discounts have a significant positive effect on positive emotions. Hedonic consumption also has a significant positive effect on impulse buying. The store environment, while not significant, has a positive effect on impulse buying. Price cuts have a significant positive effect on impulse buying. Positive emotions, while not significant, have a positive effect on impulse buying. The indirect influence hypothesis test results show that Hedonic consumption, while not significant, has a positive effect on impulse buying through positive emotions. The store environment, while not significant, has a positive effect on impulse buying through positive emotions. Price discounts, while not significant, have a positive effect on impulse buying through positive emotions.